Optimalisasi Potensi Lokal Desa Basseang melalui Inovasi Produk Saus Cabai dan Digital Marketing - Nursyawal Nacing; Wilda Widiawati; Cennawati Cennawati (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Leveraging local village potential through product innovation and digital marketing strategies is a strategic approach to supporting the economic independence of rural communities. This Community Service Program (PKM) aims to optimize the abundant chili commodities in Basseang Village by developing innovative chili sauce products based on local potential. This program is implemented through a participatory approach involving the "Harapan Baru" farmer group in a series of training and mentoring activities. The training includes processing harvested products into ready-to-sell products, packaging with attractive designs and branding, and utilizing social media as a digital marketing tool. The main objective of this activity is to increase community capacity in the technical aspects of production and promotion, as well as to create superior local products that are competitive in the wider market. The results of the activity show that the community is able to improve their skills in processing and marketing products more effectively. The innovative chili sauce has a distinctive flavor and is attractively packaged, making it popular in both local and online markets. Furthermore, the use of social media such as Instagram and WhatsApp Business provides broader and more efficient distribution access than conventional methods. Conceptually, this activity demonstrates that the integration of product innovation and digital marketing can overcome the limitations of traditional distribution and create added value for the village-based economy. This program is expected to become an empowerment model that can be replicated in other villages with similar commodity potential. Recommendations from this activity emphasize the importance of ongoing support from local governments, academics, and the private sector to ensure sustainability, develop community capacity, and systematically and sustainably expand the program's impact to other areas.